Assessment in elementary-level drama education: Teachers' conceptualizations and practices. Issue 4 (16th August 2021) - Omasta, Matt; Murray, Beth; McAvoy, Mary; Chappell, Drew
Abstract: This study is a phenomenological exploration of assessment practices in elementary-level drama education. Through analysis of interviews with fourteen drama educators, it describes how elementary drama teachers conceptualize assessment in theory and practice. Specifically, it discusses teachers' explicit definitions of assessment; the content matter they assess (and do not assess); their expectations for student performance; and the scaffolded, iterative, and formative nature of much assessment practice. The study recommends specific policy reforms at the state, district, and school levels related to ensuring appropriate assessment measures are implemented and supported; promoting teacher agency in assessment development; and increasing student access to quality drama education at the elementary level.